2005
DOI: 10.1093/ndt/gfi211
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic action of citrate in urolithiasis explained by chemical speciation: increase in pH is the determinant factor

Abstract: The therapeutic action of citrate in the management of calcium oxalate urolithiasis is due to the formation of a pH dependent calcium-citrate-phosphate complex which reduces the concentration of the free calcium ion species, thereby reducing the risk of stone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 17 publications
2
47
0
4
Order By: Relevance
“…An alkaline urine favors CaP stone formation but decreases the risk of uric acid precipitation. Using computerbased methods (EQUIL2 21 and JESS 22 ) as well as empirical physicochemical methods, Pak et al 23 showed that raising urinary pH from 6.0 to 6.5, such as we have observed in our two groups, will increase the brushite relative supersaturation In addition to defects in urinary acidification, B1 subunit mutations are associated with sensorineural hearing loss. 3,13 In this study, we did not detect obvious hearing abnormalities in recurrent SFs with the p.E161K carriers, but audiometric investigations were not performed, and thus, the effect of the p.E161K SNP on inner ear function remains unknown at the moment.…”
Section: Discussionmentioning
confidence: 64%
“…An alkaline urine favors CaP stone formation but decreases the risk of uric acid precipitation. Using computerbased methods (EQUIL2 21 and JESS 22 ) as well as empirical physicochemical methods, Pak et al 23 showed that raising urinary pH from 6.0 to 6.5, such as we have observed in our two groups, will increase the brushite relative supersaturation In addition to defects in urinary acidification, B1 subunit mutations are associated with sensorineural hearing loss. 3,13 In this study, we did not detect obvious hearing abnormalities in recurrent SFs with the p.E161K carriers, but audiometric investigations were not performed, and thus, the effect of the p.E161K SNP on inner ear function remains unknown at the moment.…”
Section: Discussionmentioning
confidence: 64%
“…This method assumes about a 50% reduction in the free calcium ion through soluble complexes formed by citrate. This provides a good representation for urine in general, but for the inhibition study here it is only an approximation because in reality the degree of speciation varies with the amount of urinary citrate (28). To account for this variation, resorting to a speciation code such as Equil2 (36) or JESS (19) is necessary.…”
Section: Effect Of Citrate Inhibitionmentioning
confidence: 99%
“…Because of its high affinity for divalent cations, citrate reduces Ca 2+ activity and thus the relative supersaturation of urine with respect to calcium-containing minerals. Citrate also causes changes in many ionic species, notably a large increase in the complex [Ca-Citrate-PO 4 ] 4-, an effect that is mainly due to alkalinization of the urine [Rodgers et al, 2006]. However, there are also direct interactions between citrate and urinary crystals, at least those of COM.…”
mentioning
confidence: 99%